(untitled) (Revista de História da UEG (REVHIST), 2019)
The objective of this work is to study the Baptist missions inaugurated in the interior of Central Brazil, beginning in 1926, through the religious, educational and social action of the teachers Beatriz Rodrigues da Silva and Lygia de Castro Martins, under the guidance of the Board of National Missions, of the Brazilian Baptist Confederation. We are interested in the work of the missionaries as social agents promoting a cultural conformation of the indigenous and sertanejas populations of the Tocantins valley, contributing to the implementation of the Baptist evangelization program, in harmony with the projects of national integration in fashion in the period. To approach the missionary actions of the two teachers, we will use theoretical references from the Cultural History of Religions, in an interface with concepts from Anthropology and Sociology, with the objective of perceiving the missionary practices as belonging to the formation of the religious field, a term anchored in Pierre’s perspective Bourdieu.